Perception and Representation of Lexical Tones in Native Mandarin-Learning Infants and Toddlers - Shi, Rushen; Gao, Jun; Achim, André; Li, Aijun (Frontiers in Psychology, 2017)
We investigated the perceptual development of lexical tones in native tone-learning infants during the first two years of life, focusing on two important stages of phonological acquisition: the preverbal and vocabulary explosion stages. Experiment 1 examined monolingual Mandarin-Chinese-learning 4- to 13-month-olds’ discrimination of similar lexical tones in Mandarin, Tone 2 (T2, rising) versus Tone 3 (T3, low-dipping). Infants were habituated to exemplars of one tone (either T2 or T3), and tested with new exemplars of the habituated tone versus the contrasting tone. Results show that looking time increased for the contrasting tone, but not for new exemplars of the habituated tone, suggesting that infants discriminated the two tones as separate categories. Experiment 2 tested whether tones are distinguished in toddlers’ lexicon. Monolingual Mandarin-learning 19- to 26-month-olds were presented with pairs of objects while one was named. Targets were familiar words bearing T2 or T3, either correctly pronounced (CP) or mispronounced (MP) in tone. We found that word recognition was equally successful in CP and in MP trials when T2 was mispronounced as T3 and T3 as T2, indicating that T2 and T3 are confusable. In contrast, recognition failed when T2 and T3 words were mispronounced as Tone 4 (T4, falling), showing that T4 was represented as a distinct category. Results show that toddlers have difficulty encoding similar tones distinctly in known words. The T2-T3 contrast is particularly challenging because of Tone 3 Sandhi, which changes T3 to T2 when it precedes another T3. At the stage when toddlers track the meaning of T2 and T3 words and track the sandhi alternations, they seem to overgeneralize the two tones as variants of one functional category, reflecting perceptual organization at the level of phonemic learning.